[Solved] CENG223 Take Home Exam 1

Click And Check all our Assignments
Click Here and Upload you Assignment for Free!

INSTANT DOWNLOAD!

100/100 Trustscore on scamadviser.com

10 USD $

Category: Tag:

Question 1

  1. Construct a truth table for the following compound proposition.

(q →¬p) ↔ (p ↔¬q)

  1. Show that whether the following conditional statement is a tautology by using a truth table.

[(p q) ∧ (r p) ∧ (r q)] → r

Question 2

Show that (p q) ∧ (p r) and (¬q ∨¬r) →¬p are logically equivalent. Use tables 6,7 and 8 given under the section ”Propositional Equivalences” in the course textbook and give the reference to the table and the law in each step.

Question 3

Let F(x, y) mean that x is the father of y; M(x, y) denotes x is the mother of y. Similarly, H(x, y), S(x, y), and B(x, y) say that x is the husband/sister/brother of y, respectively. You may also use constants to denote individuals, like Sam and Alex. You can use ∨,,,¬,,∃ rules and quantifiers. However, you are not allowed to use any predicate symbols other than the above to translate the following sentences into predicate logic. ∃! and exclusive-or (XOR) quantifiers are forbidden:

  • Everybody has a mother.
  • Everybody has a father and a mother.
  • Whoever has a mother has a father.
  • Sam is a grandfather.
  • All fathers are parents.
  • All husbands are spouses.
  • No uncle is an aunt.
  • All brothers are siblings.
  • Nobody’s grandmother is anybody’s father.
  • Alex is Ali’s brother-in-law.

1

11) Alex has at least two children.Question 4 12) Everybody has at most one mother.

Prove the following claims by natural deduction. Use only the natural deduction rules ∨, ∧, →, ¬ introduction and elimination. If you attempt to make use of a lemma or equivalence, you need to prove it by natural deduction too.

  1. p q,r s ` (p r) → (q s)
  2. ` (p → (r →¬q)) → ((p q) →¬r)

Question 5

Prove the following claims by natural deduction. Use only the natural deduction rules ∨,,,¬,,∃ introduction and elimination. If you attempt to make use of a lemma or equivalence, you need to prove it by natural deduction too.

  1. xP(x) ∨∀xQ(x) `∀x(P(x) ∨ Q(x))
  2. xP(x) → S `∃x(P(x) → S)

Reviews

There are no reviews yet.

Only logged in customers who have purchased this product may leave a review.

Shopping Cart
[Solved] CENG223 Take Home Exam 1
10 USD $